Development and validation of new SSR markers from expressed regions in the garlic genome (Scientia Agricola, 2015)
Only a limited number of simple sequence repeat (SSR) markers is available for the genome of garlic (Allium sativum L.) despite the fact that SSR markers have become one of the most preferred DNA marker systems. To develop new SSR markers for the garlic genome, garlic expressed sequence tags (ESTs) at the publicly available GarlicEST database were screened for SSR motifs and a total of 132 SSR motifs were identified. Primer pairs were designed for 50 SSR motifs and 24 of these primer pairs were selected as SSR markers based on their consistent amplification patterns and polymorphisms. In addition, two SSR markers were developed from the sequences of garlic cDNA-AFLP fragments. The use of 26 EST-SSR markers for the assessment of genetic relationship was tested using 31 garlic genotypes. Twenty six EST-SSR markers amplified 130 polymorphic DNA fragments and the number of polymorphic alleles per SSR marker ranged from 2 to 13 with an average of 5 alleles. Observed heterozygosity and polymorphism information content (PIC) of the SSR markers were between 0.23 and 0.88, and 0.20 and 0.87, respectively. Twenty one out of the 31 garlic genotypes were analyzed in a previous study using AFLP markers and the garlic genotypes clustered together with AFLP markers were also grouped together with EST-SSR markers demonstrating high concordance between AFLP and EST-SSR marker systems and possible immediate application of EST-SSR markers for fingerprinting of garlic clones. EST-SSR markers could be used in genetic studies such as genetic mapping, association mapping, genetic diversity and comparison of the genomes of Allium species.